Results of nodule detection along OFOS tracks of RV SONNE cruise SO268 - Timm Schoening (PANGAEA, 2021)
Photos were acquired by a camera (ID: SO_CAM-1_Photo_OFOS) mounted on a towed OFOS camera platform (ID: SO_PFM-01_OFOS) during research cruise SO268 of RV SONNE. Twelve deployments in different areas of the Pacific Ocean were conducted. Individual nodules were delineated in the images by the CoMoNoD algorithm (see extquotesingleRelated to extquotesingle references). Results of single nodule detection were aggregated to compute these results per image analyzed. Nodule detections below 2 square centimeters are neglected as are detections above 707 square centimeters. The result values for the nodule width correspond to the median of all nodules in that image.